SECURITIZATION OF MARITIME SECURITY ISSUES IN SUPPORTING INDONESIA’S DEFENSE DIPLOMACY AT ADMM-PLUS ON MARITIME SECURITY - Lubis, Rizky Reza (Jurnal Pertahanan dan Bela Negara, 2018)
Abstract –Indonesia is one of the countries which has many maritime security issues that needs to be managed appropriately through defense diplomacy approach, including the ASEAN framework. ADMM Plus on Maritime Security as the highest defense forum and dialog in ASEAN on maritime security issues is expected to be able to build confidence building measures and mutual trust between ASEAN member states and non-member states in solving maritime security issues. However, some goals have not been achieved due to many complex problems on maritime security in domestic sphere. This paper will use securitization theory, defense diplomacy concept, and maritime security concept for analyzing the maritime security issues in Indonesia which need securitization for supporting its defense diplomacy at ADMM Plus on Maritime Security. However, the securitization progress faced several challenges coming from various aspects, especially the habit of political leaders that only use maritime security as political instrument without concerning to the real security issues. Keywords: Maritime Security, Securitization, ADMM-Plus, Defense Diplomacy